Crystal engineering towards the luminescence property trimming of hybrid coordination polymers1. Issue 7 (21st February 2015) - Liu, Beibei; Bai, Liang; Lin, Xiaoling; Li, Kaixuan; Huang, Hui; Hu, Hailiang; Liu, Yang; Kang, Zhenhui
<x xml:space="preserve">Abstract</x> In this work, we report the synthesis, structures and luminescence properties of two pairs of isostructural coordination polymers [Cu(mttz)] (1) and [Cu(ettz)] (3); [Cu2(mttz)Cl] (2) and [Cu2(ettz)Cl] (4) (Hmttz = 5-(methylthio)-1H-tetrazole, Hettz = 5-(ethylthio)-1H-tetrazole).